Hydroxychloroquine in COVID-19 Patients: Pros and Cons - Younis, Nour K.; Zareef, Rana O.; Al Hassan, Sally N.; Bitar, Fadi; Eid, Ali H.; Arabi, Mariam (Frontiers in Pharmacology, 2020)
The pandemic of COVID-19, caused by SARS-CoV-2, has recently overwhelmed medical centers and paralyzed economies. The unparalleled public distress caused by this pandemic mandated an urgent quest for an effective approach to manage or treat this disease. Due to their well-established anti-infectious and anti-inflammatory properties, quinine derivatives have been sought as potential therapies for COVID-19. Indeed, these molecules were originally employed in the treatment and prophylaxis of malaria, and later in the management of various autoimmune rheumatic and dermatologic diseases. Initially, some promising results for the use of hydroxychloroquine (HCQ) in treating COVID-19 patients were reported by a few in vitro and in vivo studies. However, current evidence is not yet sufficiently solid to warrant its use as a therapy for this disease. Additionally, the therapeutic effects of HCQ are not without many side effects, which range from mild gastrointestinal effects to life-threatening cardiovascular and neurological effects. In this review, we explore the controversy associated with the repurposing of HCQ to manage or treat COVID-19, and we discuss the cellular and molecular mechanisms of action of HCQ.